Determinants of dividend payout ratios: evidence from colombo stock exchange (cse) in sri lanka - Elangkumaran, P. (University of Jaffna, 2012)
This study is seeks to examine the determinants of dividend payout ratios of listed companies in Colombo Stock Exchange (CSE) Sri Lanka. In this paper, Researcher has used Lintner dividend model and its extended versions for analysis of dividend determinates. Growth in sales, earnings per share, price earnings ratio, market value to book value, cash flow, leverage, liquidity and return on assets are used as independent variables while dividend payout is the dependent variable. The analyses are performed using data derived from the financial statements of twenty eight listed companies of Colombo Stock Exchange (CSE) during the period of 2010/2011. The present study used the correlation coefficient to identify the relationship between variables and linear regression to find out the associations between determinants and the dividend payout. It is found that only 37.20% of dividend payout can be explained by determinants variables. Through multiple correlation analysis it is found 60.99% correlation between dividend payout and the defined determinants variables. On the other hand considering individually there is a positive relationship between dividend payout ratios and growth in sales (GS), earning per share (EPS), market to book value (MB), liquidity (LIQ) and return on asset (ROA). And also show negative relationship between dividend payout ratio and price earnings ratio (P/E), Cash flow (CF), and leverage (LEV). The main value of this study is the identification of the factors that influence the dividend payout policy decisions of listed firms in Sri Lanka.
Keywords: Dividend payout; Colombo Stock Exchange; Market Value